LEADERSHIP CHARACTERS IN MALAYSIAN RELIGIOUS-NGOs: AN INTRODUCTORY OVERVIEW - Mhd Omar, Mohd Faridh Hafez; Syed Ismail, Sharifah Hayaati; Ilyas, Ishomuddin Sulaiman (Jurnal Syariah, 2021)
Leadership is a key function and process to unlock the effectiveness and enhancement of any organization’s development, including Religious-NGOs (RNGOs). This can be attained via three main characteristics, which are charismatic, transformational and servant leadership. Previous research has proved that these characteristics are relevant for NGOs, but little was found for RNGOs. RNGO is a form of NGO that is well-known for its active role in contributing to a harmonious and religious society. This paper focused on the concept of leadership in RNGOs and an introductory to the identity of Malaysian Islamic RNGOs that are diverse by ethnic identities. This study was qualitative in nature and depended heavily on existing literature and official reports. The study found that all three selected Islamic RNGOs that represent the Malay Muslims, Chinese Muslims and Indian Muslims adopt and practice charismatic, transformational and servant leadership in executing their organizations’ objectives, which could possibly be a yardstick to effective RNGO leadership development in the future.